Platelet Reactivity and Response to Aspirin and Clopidogrel in Patients with Platelet Count Disorders. (17th April 2021) - Kuliczkowski, Wiktor; Żurawska-Płaksej, Ewa; Podolak-Dawidziak, Maria; Cielecka-Prynda, Magdalena; Karolko, Bożena; Dębski, Jakub; Kaaz, Konrad; Protasiewicz, Marcin; Prajs, Iwona; Mysiak, Andrzej; Wróbel, Tomasz; Usnarska-Zubkiewicz, Lidia
Abstract : Background . Platelet reactivity and response to antiplatelet drugs, acetylsalicylic acid (ASA) and clopidogrel, in patients with thrombocytopenia and thrombocythemia can have a potentially important effect on the outcome. The effectiveness and safety of antiplatelet drugs in such patients has not been well examined. Measuring the effect of ASA and clopidogrel on platelets could help guide the therapy. Nevertheless, platelet response to antiplatelet drugs is not routinely measured in platelet count disorders and relevant evidence is scarce. Aims . The study aimed to measure platelet reactivity and response to ASA and clopidogrel in patients with platelet count disorders. Materials and Methods . This was a cross-sectional study of consecutive patients hospitalized in cardiology and hematology departments in the years 2018–2019. The study included patients with thrombocytopenia (PLT < 150 G/L) and thrombocythemia (PLT > 450 G/L) on ASA or dual antiplatelet therapy (DAPT; ASA plus clopidogrel). Controls included patients on antiplatelet drugs with normal platelet count. Platelet reactivity was measured in whole blood (Multiplate aggregometer, Roche, Switzerland) using arachidonic acid (AA), adenosine-5′-diphosphate (ADP), and thrombin receptor agonist peptide-6 (TRAP) as agonists. Platelet aggregation was expressed in arbitrary units (AU). AA-induced aggregation was used as a measure of response to ASA with a cut-off above 30 AU showing high on-treatment platelet reactivity to ASA (HTPR-A). ADP-induced aggregation measured response to clopidogrel with a cut-off above 48 AU for high on-treatment platelet reactivity to clopidogrel (HTPR-C). TRAP-induced aggregation measured baseline platelet reactivity not affected by oral antiplatelet drugs. Results . The study included 174 patients. There were 64 patients with thrombocytopenia, 30 patients with chronic thrombocythemia, and 80 controls. All patients were on 75 mg of ASA and 32% of them additionally on 75 mg of clopidogrel due to a history of recent coronary artery angioplasty. AA- and ADP-induced aggregation was comparable between thrombocytopenic patients and controls (median (IQR) 19 (7–28) vs. 23 (15–38) for AA AU and 32 (16–44) vs. 50 (32–71) for ADP AU, respectively), while it was significantly higher in thrombocythemic patients (median (IQR) 80 (79–118) for AA AU and 124 (89–139) for ADP AU). TRAP-induced aggregation showed significantly lowest aggregation in thrombocytopenic (median (IQR) 41 (34–60) for TRAP AU) and highest in thrombocythemic patients (median (IQR) 137 (120–180) for TRAP AU). HTPR-A was frequent in thrombocythemic patients in comparison with thrombocytopenic patients and controls (60% vs. 4% vs. 15%, respectively; p < 0.0002 ). HTPR-C was highly common in thrombocythemic patients and least common in thrombocytopenic ones in comparison with controls (80% vs. 8% vs. 40%, respectively; p < 0.001 ). Conclusion . Chronic thrombocytopenia does not significantly affect platelet reactivity and response to ASA and clopidogrel in comparison with controls. Thrombocytosis significantly increases platelet reactivity and attenuates response to both ASA and clopidogrel.